Melatonin Mitigates Oxazolone-Induced Colitis in Microbiota-Dependent Manner - Zhao, Zi-xiao; Yuan, Xi; Cui, Yan-yan; Liu, Jun; Shen, Jing; Jin, Bi-ying; Feng, Bing-cheng; Zhai, Yun-jiao; Zheng, Meng-qi; Kou, Guan-jun; Zhou, Ru-chen; Li, Li-xiang; et al. (Frontiers in Immunology, 2022)
Abstract Type 2 cytokines increase in the blood and intestinal tissues of UC patients in active phase, indicating the participation of type 2 immune response in the UC progression. The beneficial effects of melatonin on DSS and TNBS colitis model have been illustrated, but its role in oxazolone (Oxa)-induced colitis model driven by type 2 immune response remains elusive. We investigated the relationship between the concentration of melatonin and the severity of ulcerative colitis, which showed a significant negative correlation. Subsequently, we detected the effect and potential mechanisms of melatonin in Oxa-induced colitis mice. Administration of melatonin significantly reduced body weight loss, colon shortening, as well as neutrophil infiltration in Oxa-induced colitis mice. Melatonin treatment also mitigates Oxa-induced colitis by suppressing type 2 immune response. In addition, we used western blotting assays and found that melatonin attenuated intestinal permeability by enhancing the expression of ZO-1 and Occludin in colitis mice. Interestingly, the protection by melatonin was abolished when mice were co-housed, indicating that the regulation of gut microbiota by melatonin was critical in alleviating Oxa-induced colitis. Afterwards, 16S rRNA sequencing was performed to explore the microbiota composition, which showed a decreased richness and diversity of intestinal microbiota on OTU level after melatonin treatment. Melatonin also caused elevation of Bifidobacterium, a kind of well-known probiotics, and reduction of several harmful bacterial genus, such as Desulfovibrio, Peptococcaceae and Lachnospiraceae. Fecal microbiota transplantation (FMT) was used to explore the necessity of microbiota for the function of melatonin in Oxa-induced colitis. We noticed that Microbiota transplantation from melatonin-treated mice alleviated Oxa-induced colitis, suggesting microbiota was required for the relief of Oxa-induced colitis by melatonin. Taken together, our findings demonstrate that melatonin ameliorates Oxa-induced colitis in microbiota-dependent manner, suggesting the therapeutic potential of melatonin in UC by targeting type 2 immune response.